Calcified amorphous tumor of the heart in a hemodialysis patient. Issue 12 (12th August 2016) - Takeuchi, Tetsushiro; Dohi, Kaoru; Sato, Yuichi; Kanemitsu, Shinji; Sugiura, Saki; Uchida, Katsunori; Yamada, Norikazu; Takeuchi, Misao; Shiraishi, Taizo; Shimpo, Hideto; Ito, Masaaki
Abstract : We report a case of calcified amorphous tumor (CAT) of the heart in a 60‐year‐old Japanese man on hemodialysis. Because the masses in the mitral annulus developed during two‐year echocardiographic follow‐up, he underwent surgical resection with mitral valve replacement. Histological examination showed that the tumor contained multiple calcified nodules, which confirmed the diagnosis of CAT. This case report reinforces the need to deeply and periodically investigate for cardiac involvement of CAT in all patients on hemodialysis.